The Removal of Millers Point Public Housing Tenants in Inner-Sydney by the New South Wales Government: Narratives of Government and Tenants. Issue 4 (2nd October 2017) - Morris, Alan
Abstract: In 2014, the New South Wales (NSW) government announced that it was to move all of the approximately 580 public housing tenants from Millers Point, Dawes Point and The Rocks in inner Sydney, sell the properties and use the proceeds to build social housing. This article, drawing on government media material and in-depth interviews with tenants, examines the removal process and contrasts the government's narrative with that of the tenants. What is argued is that the displacement reflects how in the current neoliberal climate, instrumental rationality is a central feature, i.e. little cognisance is taken of the human cost of policies.